Hubungan Status Gizi dengan Persistensi Gigi Sulung pada Anak Usia 13 –15 Tahun di Smpn 5 Padang - Nurul Trinanda Rizal; Emriadi Emriadi; Murniwati Murniwati (Faculty of Dentistry Universitas Andalas, 2017)
Over-retained primary tooth is a condition of deciduous tooth that is retained beyond time of exfoliation, which should completely exfoliate at the end of the age of 12 years. This condition can cause delay in eruption of permanent tooth and thus lead to malocclusion and other orthodontic problems. One of the several reasons this condition happen is malnutrition. The purpose of this research is to determine the correlation between nutritional status and over-retained primary tooth among children aged 13 to 15 years at Junior High School 5 of Padang City. This research was an analytic observational study. The respondents were 95 students of Junior High School 5 of Padang. Respondents chosen with a Proportionate Stratified Random Sampling. This study determine that there are about 21,1% underweight respondents and 78,9% normal-overweight respondents. There are 45 retained primary teeth from 24 respondents. About 25,3% respondents had over-retained primary tooth with the highest prevalence occurred in maxilla with the mostly retained teeth was left canine (20%). From the Chi-Square test obtained p value = 1 is greater than the value that is meaningful probability (>0,05) which means there is no a significant correlation between nutritional status and over-retained primary tooth among children aged 13 to 15 years. The conclusion is there is no a significant value correlation between nutritional status and over-retained primary tooth among children aged 13 to 15 years.